POPULATION STRUCTURE AND MORFOMETRIC CHARACTERISTICS OF MUSSELS (Corbicula javanica) IN THE RICE FIELD IRRIGATION OF PAK BULU VILLAGE, ANJONGAN SUB-DISTRICT, MEMPAWAH DISTRICT - LIDIA BERLIANA PARDEDE; Inpurwanto Inpurwanto; Widadi Padmarsari Soetignya (Jurnal Sains Pertanian Equator, 2020)
ABSTRACTResearch on the population structure and morphometric characteristics of mussel (Corbicula javanica) in the rice field irrigation of Pak Bulu Village, Anjongan Sub-district, Mempawah District was conducted from March to May 2020. This research aims to determine the population structure including density, distribution, and morphometric characters of mussels in the rice field irrigation of Pak Bulu Village, Anjongan Sub-district, Mempawah District. It used a purposive random sampling method in which the research location of selection stations based on differences in the environmental setting. The location of divided into three areas, namely are station I (located near the secondaring forest), area II (closed to the dam and residential areas), and area III (located around the dam). Each station consists of 2 transects with a length of 200 m and within the transect there are 15 quadrate meansuring 1x1 m. Based on the result of the research, the average population density between areas is 43.35 ind/m2 and the range is between 8.61 - 81.85 ind/m2. The distribution of mussels is categorized as clumped. Meanwhile, the morphometric characteristics of mussels of shell length (PC), shell height (TC), shell thickness (TBL), and total weight (BT) show varied sizes between areas. The growth pattern of mussel shells in area I shows a negative allometric growth pattern. Meanwhile, area II and area III show isometric and allometric positive respectively.  Keywords: Mussels, Population Structure, Morphometric Characteristics